KINERJA REKSA DANA SAHAM PASCA KRISIS SUBPRIME MORTGAGE - Mohammad Adam; Isnurhadi .; Muizzuddin .; Luthfiyah . (Program Studi Magister Manajemen FE Unsri, 2016)
The purpose of this study is to analyze the performance of mutual funds shares after the subprime mortgage crisis. The population in this study are 55 mutual funds shares of 34 mutual funds investment managers who are issuing shares and mutual funds in the capital market. The sampling technique in this study uses a non-probability sampling which is a kind of purposive sampling based on certain criteria. Based on the criteria are obtained as many as 20 mutual funds. In addition, this study also uses quantitative analysis techniques, namely the analytical technique in the calculation of the performance of a portfolio of index mutual funds by Sharpe, Treynor and Jensen. The result shows that during the observation period, namely the post-crisis Subprime Mortgage, of 20 mutual funds are included in the study criteria, there are quite a lot of mutual fund shares are able to rebound and its performance are able to outperform the market as compared with mutual funds which are underperform.